Classification of European bog vegetation of the Oxycocco‐Sphagnetea class. Issue 1 (24th March 2022) - Jiroušek, Martin; Peterka, Tomáš; Chytrý, Milan; Jiménez‐Alfaro, Borja; Kuznetsov, Oleg L.; Pérez‐Haase, Aaron; Aunina, Liene; Biurrun, Idoia; Dítě, Daniel; Goncharova, Nadezhda; Hájková, Petra; Jansen, Florian; et al.
Abstract: Aims: Classification of European bog vegetation ( Oxycocco‐Sphagnetea class); identification of diagnostic species for the class and vegetation subgroups (orders and alliances); development of an expert system for automatic classification of vegetation plots; and production of distribution maps of the Oxycocco‐Sphagnetea class and its alliances. Location: Europe. Methods: A data set of vegetation‐plot records was compiled to include various bog types over most of the European continent. An unsupervised classification (beta‐flexible linkage method, Sørensen distance measure) and detrended correspondence analysis (DCA) ordination were applied. Formal definitions of syntaxa based on species presence and covers, and respecting the results of the unsupervised classification, were developed and included in a classification expert system. Results: The Oxycocco‐Sphagnetea class, its two orders ( Sphagno ‐ Ericetalia tetralicis and Sphagnetalia medii ) and seven compositionally distinct alliances were formally defined. In addition to the syntaxa included in EuroVegChecklist, three new alliances were distinguished: Rubo chamaemori ‐ Dicranion elongati (subarctic polygon and palsa mires); Erico mackaianae ‐ Sphagnion papillosi (blanket bogs of the northwestern Iberian Peninsula); and Sphagno baltici ‐ Trichophorion cespitosi (boreal bog lawns). The latter alliance is newly described in this article. Conclusions: This first pan‐European formalized classification of European bog vegetation partially followed the system presented in EuroVegChecklist, but suggested three additional alliances. One covers palsa and polygon mires, one covers Iberian bogs with endemics and one fills the syntaxonomical gap for lawn microhabitats in boreal bogs. A classification expert system has been developed, which allows assignment of vegetation plots to the types described. Abstract : Seven alliances were formally defined in Europe within the Oxycocco‐Sphagnetea class. Rubo chamaemori ‐ Dicranion elongati (subarctic polygon and palsa mires), Erico mackaianae ‐ Sphagnion papillosi (blanket bogs of the northwestern Iberian Peninsula), and Sphagno baltici ‐ Trichophorion cespitosi (boral bog lawns) together with four alliances included in EuroVegChecklist. A classification expert system has been developed, which allows assignment of vegetation plots to bog alliances.